Preoperatively Identified Sarcopenia Leads to Increased Postoperative Complications, Hospital and ICU Length of Stay in Autologous Microsurgical Breast Reconstruction - Pittelkow, Eric M.; DeBrock, Will C.; McLaughlin, Briana E.; Hassanein, Aladdin H.; Socas, Juan; Lester, Mary E.; Duquette, Stephen P. (Journal of Reconstructive Microsurgery, 2020)
Background Sarcopenia is a condition characterized by the loss of skeletal muscle mass and strength. Recently, there has been a tremendous amount of research into the prognostic value of sarcopenia in surgical outcomes. The purpose of this study was to compare postoperative outcomes in free flap breast reconstruction in patients with and without sarcopenia.Methods One hundred three patients who underwent autologous breast reconstruction from 2013 to 2016 were studied. The cross-sectional area (CSA) of skeletal muscle was measured from preoperative computed tomography images at L3 using the National Institutes of Health ImageJ software. CSA was then normalized to patient stature by dividing CSA by height (cm2/m2). A previously published skeletal muscle index cutoff of 38.5 cm2/m2 was used to define sarcopenia. Intraoperative and postoperative surgical outcomes were recorded retrospectively. Outcomes were analyzed using multivariate, univariate, and regression statistics.Results Eight of the 103 (7.8%) patients were found to have sarcopenia. Sarcopenia was associated with a statistically significant increase in flap site delayed healing (37.5% vs. 20%, p = 0.046), take back to the operating room (25% vs. 11.6%, p = 0.05), intensive care unit length of stay (1.5 vs. 0.02 days, p < 0.0005), and hospital length of stay (8.38 vs. 5.49 days, p < 0.0005) when compared with patients without sarcopenia. There were no significant differences in flap loss, surgical site infection, hematoma, seroma, donor site delayed healing, intraoperative complications, and number of revision surgeries.Conclusion Sarcopenia is significantly associated with increased complications in patients undergoing free flap breast reconstruction. Further investigation into the biochemical and physiologic changes associated with sarcopenia is needed.
Keywords: sarcopenia; microsurgery; breast reconstruction